Single-Center Outcomes of Autologous Hematopoietic Stem Cell Transplantation Accompanied by High-Dose Chemotherapy in Patients with Solid Organ Tumors - Levent Ündar; Ozan Salim; Sema Sezgin Göksu; Utku Iltar; Ünal Ataş; Orhan Kemal Yücel; Ayşe Tan Doğruel (Acta Medica Alanya)
Aim: In contrast to hematologic diseases, the use of hematopoietic stem cell transplantation (HCT) for solid organ tumors is limited, with recommendations available only for certain selected diagnoses and cases. Methods: Data from 16 adult patients who underwent HCT with a diagnosis of solid organ tumor between 2006-2023 were analyzed.Results: The median age of the patients was 36.5 years (21–46), and 13 (81.2%) were male. Seven patients (43.7%) had testicular germ cell tumors (GCT), four (25%) had Ewing sarcoma, and five (31.3%) had other solid organ tumors. Autologous HCT was performed in 14 patients (87.5%) due to relapsed/refractory disease, and only five patients (31.3%) achieved a complete response to salvage therapy prior to transplantation. Post-transplant relapse occurred in 92.8% of patients, with a median progression-free survival (PFS) of 6.5 (2-32) months. Fourteen patients (87.5%) died, including two during transplantation, with a median overall survival (OS) of 53.0 (9–213) months. Although the median PFS for testicular GCT patients after autologous HCT was longer than that of other patients (12.0 vs. 4.5 months; p=0.04), the median OS was similar (90.0 vs. 46.0 months; p=0.52).Conclusion: The literature regarding the role of HCT in solid organ tumors is generally based on retrospective data and periods when older treatment approaches are employed. With the current use of immunotherapy and targeted therapies, both the necessity and stage at which HCT should be performed should be further investigated, and new studies are needed to address this issue.